A Survey on Using Iranian National Medical Digital Library (INLM) as An Educational Intervention - Aram Tirgar; Mousa Yaminfirooz; Zahra Dehghan (Babol University of Medical Sciences, 2013)
ABSTRACT BACKGROUND AND OBJECTIVE: Iranian National Medical Digital Library (INLM) was started in 2008 in order to facilitate accessibility to the newest scientific resources for all medical universities. The aim of this study was to discover the condition of using this scientific intervention among the users in Babol University of Medical Sciences. METHODS: This cross-sectional study was conducted among 91 faculty members and research center staffs (who were INLM members) during 4 related workshops in summer 2010. The data were collected by means of a tailor-made data collection sheet and was analyzed by means of SPSS16 and using descriptive and analytical statistical indices. FINDINGS: Sixteen defected questionnaires out of 91 were omitted. From the rest completed questionnaires (n=75), 34 were women, 38 were PhD, and half of them have not been trained about INLM yet.58 persons were faculty members and 59 individuals had experienced downing articles from INLM before the workshops and 16 none. 91% of participants expressed on INLM necessity and its effectiveness for quantitative and qualitative improvement of education and research activities. Sciencedirect and Ovid were the more familiar data bases among users, and Ebsco and Scopus were less familiar. 68% of participants had difficulties about web speed, lack of information and human resources for guidance, limitation in the access to some of resources, and incorrect filtering. CONCLUSION: Although a huge investment was done to extend rapid accessibility to the newest scientific resources, a considerable number of faculty members were not aware and trained, and many of them had several difficulties in effective use of INLM.